Medical students’ psychological wellbeing and their overall academic performance —a correlational study - Ansari, Sadaf Konain; Al-Eraky, Mohammad; Yasmeen, Rahila (Pakistan Journal of Physiology, 2019)
Background: This study examines the undergraduates building the best of institutional situation by rising from it or seeing it in a more encouraging light. The objectives of the study were to measure the correlations of psychological wellbeing of medical students with overall academic performance in different institutions, and to compare medical students’ psychological wellbeing scores with respect to their medical institutions and gender. Methods: This study was conducted from January to June 2018 in two different medical institutes. After the ethical approval from the institutions a purposive non-probability sampling was done. A quantitative correlational descriptive design was used to collect data through self-reporting 42-item Ryff Psychological Wellbeing Scale (RPWBS). This data was checked for normality by applying Kolmogorov-Smirnov (K-S test) test, and statistical analysis was calculated through SPSS-21. Results: The comparison of the median of the Ryff psychological wellbeing subscales shows that autonomy (med=21.00, IQR=7–21) was the highest median. Spearman’s correlation for institute X showed that the correlation of overall academic performance with PWB subscale was strongly positive (+1) and greater than scores in institute Y. In both institutes the relationship is significant (p<0.01). Comparative analysis shows that institute Y had highest values (p<0.000). Conclusion: More attention assigned considering every students as an individual case.